Intersecciones tipo diamante divergente, análisis de implementación en ciudades colombianas - Hernán Porras Díaz; Yerly Fabián Martínez Estupiñan (Tecnura, 2011)
The diverging diamond-like junctions are a special type of very recent design alternative in the world for confl ict resolution road, its basic function is to change the traffi c light controlled fl ow directions and so far its implementation in countries Latin America is zero, which is a waste of your benefi ts. This work has been a processof gathering information about the design, use and operation of such intersections in the world, we have analyzed the existing modelsrelated to vehicle operation and traffi c lights to control. This whole process has been applied to analysis of a specifi c case in the city of Bucaramanga, where vehicular demand as in other Colombian cities is exceeding the supply offered by the existing road infrastructure, using different simulation scenarios for comparing andmeasuring the degree of impact of each of the parameters chosen.